PENGGUNAAN SELAPUT AMNION SEGAR PADA INSISI LUKA OPERASI SEKSIO SESAREA - Adnani, Syahredi Syaiful; Bachtiar, Hafni (Fakultas Kedokteran Universitas Andalas, 2017)
In the last few decades, the incidence of caesarean section is increasing in the world, especially in Indonesia. One of the way to treat tissue scar is through biologic and synthetic dressing where nowadays, amnion has been used as biologic dressing frequently. This study was conducted to determine the effect of the use of fresh amniotic membrane on wound incision Caesarean section compared with Caesarean section incision wound covered using regular gauze bandages and fixated with plaster in RS. Dr. Reksodiwiryo Padang. The design of this study is an experimen-tal study with Post test design with control group design. Sampling was done using a formula consecutive sampling two different test samples obtained an average of 72 people for each group. The analysis used include univariate and bivariate analyzes. The average wound healing time the difference was statistically significant (p value <0.05) in the treatment and control groups. There was highly significant difference in the proportion of local infection on day 3 between the treatment and control groups (p value <0.05). There were very significant differences in the proportion of local allergic reactions at day 3, and 5 between the treatment and control group (p <0.05). There are significant differences in terms of the cost of care per day between treatment and control groups (p <0.05). From this study, the average wound healing time has a very significant difference.Keywords: Fresh Amniotic Membrane, Wound Cesarean Section, Wound Healing